1D cyclic yield model independent of load spectrum characteristics and its application to Inconel 718. (June 2017) - Klotz, T.; Blas, S.; Lévesque, M.; Brochu, M.
Highlights: Inconel 718 continuously soften under low cycle fatigue conditions. The stabilized softening rate does not depend on the maximum plastic deformation. At room temperature and under fully reversed plastic deformation cycles, Inconel 718 softening behavior is dependent on the accumulated plastic strain, irrespectively of the strain spectrum. Inconel 718 cyclic stress response during constant or complex strain controlled LCF loadings can be predicted using a data set results obtained from a different fully reversed strain spectrum. Abstract: At room temperature, nickel-based superalloy Inconel 718 softens under fully reversed plastic deformation cycles. Chaboche's unified constitutive equations have been previously used in the literature to predict nickel-based superalloy cyclic softening behavior. To better fit our results, the constitutive equations were modified to account for continuous softening. Moreover, applying the model to results gathered from two different loading spectrum indicates that the isotropic evolution is solely dependent on the accumulated plastic strain and can be applied to a variety of number of cycles and strain amplitudes combinations without adjusting the parameters. This new information is significant and has a considerable impact on material testing and modeling. It implies that a unique set of parameters extracted from any fully reversed strain controlled test can characterize the material flow stress evolution with accumulated plastic strain independently of the strain sequence, for R ɛ = − 1 . This flexible prediction method could lead to significant experimental costs reductions.